Analisis Kemampuan Berpikir Kreatif Matematis Siswa SMP Kelas VII Pada Materi Segitiga dan Segiempat - Siti Robiah Al Adawiah; Siti Rukoyah Rumbiyah; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to determine and analyze how students' mathematical creative thinking skills in working on mathematical problems, especially in triangular and quadrilateral material. The subjects of this study were students of class VII C at Darul Falah junior high school Cihampelas, West Bandung Regency. The instruments used were written tests in the form of essays which numbered 5 questions and consisted of 4 indicators of mathematical creative thinking abilities. This research method uses descriptive analysis, in order to find out the students' mistakes in solving problems. Processing data is calculated in the form of an average, the results of the data obtained by indicators of fluency presented in question 1 and question 3 produces an average of 4 and 3.23, on the flexibility indicators presented in question 2 obtain an average of 3, then in question 4 which includes the organility indicator, it gets an average of 3.16, and finally the elaboration indicator in question 5 gets an average of 2.66, then the authors conclude that the ability to think creatively in grade VII C at Darul Falah junior high school Cihampelas, on triangles and square material is included in the medium category.